(untitled) (ModaPalavra e-periódico, 2009)
In this paper I propose a reflection on the advertisements placed in magazines by fashion advertiser Colcci. Colcci is one of the AMC Têxtil Group brands, and in the last years has been active in the domestic and international markets. The general objective of this paper is to analyze the importance of language in Fashion advertisements in Santa Catarina’s scenario. In order to raise subsidies to enrich this reflection, we shall be analyzing bibliographic material about fashion, language and communication, as well as analyzing magazine advertisements for the 4 latest Colcci collections. From the material analyzed, it can be seen that fashion communication still persists in placing a pretty image to represent its collection. Fashion brands have more potential than simply presenting an übber model as the ad girl. The disclosure of values, brand characteristics, as well as of the collections, would not be simply to make fashion equal to any other product. The information about fashion can add value to the product and have old and new customers identify with the brand and the new collections.